2017
DOI: 10.1111/add.14097
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported marijuana use over 25 years and abdominal adiposity: the Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: Neither cumulative marijuana use nor current marijuana use is associated with total abdominal, visceral, subcutaneous, or intermuscular adipose tissue, or liver attenuation in mid-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…28 A 2016 review on cannabis and cardiovascular disease reported an association between acute exposure to cannabis and transient increase in heart rate; its use may stimulate the sympathetic nervous system, 24 but repeated exposure may lower heart rate because it reduces sympathetic and enhanced parasympathetic activity. 30 Cannabis users may build up tolerance after a few days of use, shifting their autonomous nervous balance and reducing heart rate. [25][26][27][28][29]31 Prospective cohort studies suggested that risk of cardiovascular disease continuously increases with heart rate over 60 beats per minute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 A 2016 review on cannabis and cardiovascular disease reported an association between acute exposure to cannabis and transient increase in heart rate; its use may stimulate the sympathetic nervous system, 24 but repeated exposure may lower heart rate because it reduces sympathetic and enhanced parasympathetic activity. 30 Cannabis users may build up tolerance after a few days of use, shifting their autonomous nervous balance and reducing heart rate. [25][26][27][28][29]31 Prospective cohort studies suggested that risk of cardiovascular disease continuously increases with heart rate over 60 beats per minute.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,23 A 2016 review on cannabis and cardiovascular disease reported an association between acute exposure to cannabis and transient increase in heart rate, 24 but repeated exposure over a few days lowered heart rate in various studies. [25][26][27][28][29][30][31] These studies were small and often lacked adjustment for confounders such as physical activity, multiple cardiovascular risk factors, and medication use affecting heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…One group analyzed results from the 25-year follow-up (n = 2902) and found that years of cannabis use was inversely associated with BMI. Additionally, participants with the most years of cannabis usage (>5 years) had the lowest volumes of abdominal and subcutaneous fat, but these findings did not withstand corrections for age, sex, race, and education [ 127 ]. A similar study utilizing data from the NHANES revealed that lower BMI and waist circumference was characteristic of current cannabis users [ 128 ].…”
Section: The Relationship Between Cannabis Use and Body Weightmentioning
confidence: 99%
“…Much of the current literature is observational from longitudinal cohort studies. For example, data from the CARDIA study has reported that cannabis smokers had no increased rates of CVD or CVD risk markers, had no difference in arterial calcium levels, had lower levels of visceral adipose tissue, lower fasting glucose and insulin, and lower waist circumference and body mass index (Auer et al., 2018 ; Bancks et al., 2018 ; Jakob et al., 2021 ; Penner et al., 2013 ; Reis et al., 2017 ). Conversely, data from the same study indicated an increased risk of prediabetes (but not diabetes) with current cannabis use or high lifetime exposures (Bancks et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%